USING THE LITERATURE OF AYAT-AYAT CINTA 2 FOR THE NEXT GENERATION OF BEST CHARACTER AND INTELLIGENT - Anis Kurnia Miftahul Husna; Andayani Andayani; Suyitno Suyitno (Fakultas Bahasa dan Seni UNP, 2018)
This research article aims to explain and describe the relevance of novel Ayat-Ayat Cinta 2 with literary learning materials in high school. This study is a qualitative descriptive study with the object of research in the form of novel by Habiburrahman El Shirazy that is Ayat-Ayat Cinta 2. Technique of data collecting using purposive sampling technique according to subject matter. Data analysis techniques in this study are interactive models, including data collection, data reduction, data presentation, and conclusions. The conclusions are based on deductive techniques, which is to explain in general to the specific facts as the final conclusion. The result of this study is that it can be used as a literary learning material in SMA based on story structure and moral values that can be followed by studying students according to curriculum requirement. Ayat-Ayat Cinta 2 is full of fascinating values that can motivate students to achieve the highest education, religious, tolerant, not easily ignited issues and social life in the midst of a pluralistic Indonesian societyBERMEDIUMKAN SASTRA AYAT-AYAT CINTA 2 PEMBENTUK GENERASI PENERUS BANGSA YANG BERKARAKTER KUAT DAN CERDAS AbstrakArtikel penelitian ini bertujuan untuk menjelaskan dan mendeskripsikan relevansi novel Ayat-Ayat Cinta 2 dengan materi pembelajaran sastra di SMA. Kajian ini merupakan kajian deskriptif kualitatif dengan objek penelitian berupa novel karya Habiburrahman El Shirazy yaitu Ayat-Ayat Cinta 2. Teknik pengumpulan data dilakukan dengan teknik pusposive sampling sesuai dengan pokok permasalahan yang dikaji. Teknik analisis data dalam penelitian ini adalah model interaktif, meliputi pengumpulan data, reduksi data, penyajian data, dan penarikan kesimpulan. Simpulan dibuat berdasarkan teknik deduktif, yaitu menjelaskan secara umum menuju fakta-fakta khusus sebagai simpulan akhir. Hasil dari kajian penelitian ini adalah dapat dijadikanya novel Ayat-Ayat Cinta 2 sebagai materi pembelajaran sastra di SMA berdasarkan struktur cerita dan nilai moral yang dapat diteladani siswa dengan mengkajinya sesuai dengan tuntutan kurikulum. Ayat-Ayat Cinta 2 penuh dengan nilai-nilai pembangun jiwa yang dapat memotivasi siswa untuk mencapai pendidikan tertinggi, religius, bertoleransi, tidak mudah tersulut isu dan berjiwa sosial di tengah kondisi masyarakat Indonesia yang majemuk